Asylum Seekers and HIV/AIDS: Legal Issues, WellBeing and Fundamental Rights - Kogovšek Šalamon, Neža (Medicine, Law & Society, 2016)
Migrants, including asylum seekers, are a key population to focus on, according to the European Action Plan for HIV/AIDS 2012–2015. In general, data on the prevalence of HIV/AIDS among asylum seekers are scarce, but some receiving states have already noted a high HIV prevalence among asylum seekers who give birth. While there are many challenges in ensuring asylum seekers living with HIV/AIDS have access to adequate health services, it seems that protection of rejected asylum seekers (and other irregularly staying migrants) living with HIV/AIDS will be at the forefront of their struggle for adequate protection of their human rights.
Keywords: asylum; international protection; HIV; non-refoulement; fundamental rights